A real-time analytical steady-state calculation in power system restoration: Managing uncertainty - Noureyeh Zahiroddin; Mahtab Khalilifar; S. Mohammad Shahrtash; Shahram Jadid (Results in Engineering)
The comprehensive strategy for steady-state overvoltages caused by the energization of lightly loaded transmission lines is an essential part of power system restoration plans. In this context, dispatchers must address three key questions: (1) the required load along the restoration path, (2) the suggested reaction in the event of uncertainty or a lack of the required load, and (3) the potential impact of this loading on the voltages along the restored network. The primary purpose of this paper is to propose an analytical tool that equips dispatchers with a non-iterative, robust, and rapid solution to these questions. The main idea involves substituting restored transmission lines with an equivalent no-load line. Subsequently, the necessary optimized load amount is computed by putting together the equivalent no-load model of the restored network along with the actual length of any new line that will be energized. In this method, considerations for reactor/load uncertainty are included as well. Finally, the overall voltage assessment is conducted by applying the proposed formulation to the energized paths. The efficacy of the proposed model is substantiated by load flow results from DIgSILENT, demonstrating the method's capability to provide comprehensive loading solutions with high accuracy. This paper introduces a robust procedure as a novel advancement in the journey toward smarter transmission networks.